Clinical Guide for Family Physicians to Manage Type 2 Diabetes - Seyed Esmaeil Managheb; Mesbah Shams; Mahmood Soveid; Mohamad Hadi Imanieh; Mohsen Moghadami (Shiraz University of Medical Sciences, 2015)
Compiling clinical guidelines is one of the requirements of family physician plan and classification of health care services.1 The high prevalence of type 2 diabetes can easily be seen in general practice so that 2.5% of referrals to general practitioners are due to diabetes. More than half of the patients with Type 2 diabetes are left undiagnosed and most of them suffer from its complications at the time of diagnosis. For example, 6.2% of patients suffer from diabetic retinopathy at the time of diagnosis.2 Most patients diagnosed with diabetes take more than one type of medication to treat the complications; about 60% take only oral medications, and 14 percent take oral medications and insulin.3 Although the principles of care for people with Type 2 diabetes is well known, there is a gap between the quality of care in general practice and optimal care so that up to 50% of patients' condition are weakly controlled.4 Chronic care model for patients with chronic diseases explains the necessary measures to improve the care of people with chronic diseases. These elements include supporting disease management by the patients themselves, patient care, and support teams. Consultation and training are often done in general practice while it is usually a brief consultation about weight, medication or exercise. There is little evidence that mere printed texts are effective in controlling the disease. Extensive training programs are designed to develop self-management skills for diabetes control.4 The implementation of clinical guidelines in medical practice is a challenging task. But, a number of evidences have been shown to accelerate effective clinical guideline implementation and care improvement.5 Management of diabetes mellitus type 2 is shown in Figure 1.